Genre Transformation of the Fairy Tale in Contemporary Russian Literature - Zueva, Ekaterina; Shalneva, Tatiana Vasilieva; Osovskiy, Oleg (Journal of History Culture and Art Research, 2017)
This research is devoted to some peculiarities of structure and semantics of contemporary Russian fairy tale. The analyzed genre model is quite actual in the literature of modern turn of the centuries. It is actualized in the creativity of L. Petrushevskaya, A. Kabakov, B. Akunin, M. Fray, D. Bykov, etc. This is connected with the universality of themes and problems and the dynamics of structure of genre analyzed. Modern literature process suggests the use of various genre forms (including fairy-tale one) in the context of realization of game strategies of world construction with the deconstruction principle domination. The usage of the most productive for such kind of research methods (structural-semantical and comparative ones) gives grounds for understanding the specifics of realization of deconstruction principle through the variety of forms and meanings. For example, the scheme of “genre memory” is widely used in contemporary fairy tale. If that scheme deals with the sphere of semantics, then structural components are actively deconstructed (e.g. fairy tales by L. Petrushevskaya). If the meaningful fairy tale composition models are actualized, then the semantic component is widely transformed (e.g. Moscow Fairy Tales by A. Kabakov). The most important peculiarity of contemporary fairy tale is the integration of fairy tale, legendary, mythological and literary plots to the one game system. The result of this is on the one hand travestying of the iconic plots, on the other hand achieving the new meanings due to including context mechanisms.